Tannic acid supplementation in the diet of Holstein bulls: Impacts on production performance, physiological and immunological characteristics, and ruminal microbiota - Wang, Zuo; Zhao, Yuan; Lan, Xinyi; He, Jianhua; Wan, Fachun; Shen, Weijun; Tang, Shaoxun; Zhou, Chuanshe; Tan, Zhiliang; Yang, Yanming (Frontiers in Nutrition, 2022)
This study was conducted to evaluate the influences of supplementing tannic acid (TA) at different doses on the production performance, physiological and immunological characteristics, and rumen bacterial microbiome of cattle. Forty-eight Holstein bulls were randomly allocated to four dietary treatments: the control (CON, basal diet), the low-dose TA treatment [TAL, 0.3 % dry matter (DM)], the mid-dose TA treatment (TAM, 0.9 % DM), and the high-dose TA treatment (TAH, 2.7 % DM). This trial consisted of 7 days for adaptation and 90 days for data and sample collection, and samples of blood and rumen fluid were collected on 37 d, 67 d, and 97 d, respectively. The average daily gain was unaffected (P > 0.05), whilst the ruminal NH3-N was significantly decreased (P < 0.01) by TA supplementation. The 0.3 % TA addition lowered (P < 0.05) the levels of ruminal isobutyrate, valerate, and tumor necrosis factor alpha (TNF-α), and tended to (P < 0.1) increase the gain to feed ratio. The digestibility of DM, organic matter (OM), and crude protein, and percentages of butyrate, isobutyrate, and valerate were lower (P < 0.05), while the acetate proportion and acetate to propionate ratio in both TAM and TAH were higher (P < 0.05) than the CON. Besides, the 0.9 % TA inclusion lessened (P < 0.05) the concentrations of glucagon and TNF-α, but enhanced (P < 0.05) the interferon gamma (IFN-γ) level and Simpson index of ruminal bacteria. The 2.7 % TA supplementation reduced (P < 0.05) the intake of DM and OM, and levels of malondialdehyde and thyroxine, while elevated (P < 0.05) the Shannon index of the rumen bacterial populations. Moreover, the relative abundances of the phyla Fibrobacteres and Lentisphaerae, the genera Fibrobacter and Bradyrhizobium, and the species Bradyrhizobium sp., Lachnospiraceae bacterium RM29, and Lachnospiraceae bacterium CG57 were highly significantly (q < 0.01) or significantly (q < 0.05) raised by adding 2.7 % TA. Results suggested that the TA addition at 0.3 % is more suitable for the cattle, based on the general comparison on the impacts of supplementing TA at different doses on all the measured parameters.